Uncovering the diversification history of marine tetrapods: Ecology influences the effect of geological sampling biases - Benson, R; Butler, R (2011)
Mesozoic terrestrial vertebrates gave rise to sea-going forms independently among the ichthyosaurs, sauropterygians, thalattosaurs, crocodyliforms, turtles, squamates, and other lineages. Many passed through a shallow marine phase before becoming adapted for open ocean life. This allows quantitative testing of factors affecting our view of the diversity of ancient organisms inhabiting different oceanic environments. We implemented tests of correlation using generalized difference transformed data, and multiple regression models. These indicate that shallow marine diversity was driven by changes in the extent of flooded continental area and more weakly influenced by uneven fossil sampling. This is congruent with studies of shallow marine invertebrate diversity and suggests that 'common cause' effects are influential in the shallow marine realm. In contrast, our view of open ocean tetrapod diversity is strongly distorted by temporal heterogeneity in fossil record sampling, and has little relationship with continental flooding. Adaptation to open ocean life allowed plesiosaurs, ichthyosaurs and sea turtles to 'escape' from periodic extinctions driven by major marine regressions, which affected shallow marine taxa in the Late Triassic and over the Jurassic-Cretaceous boundary. Open ocean taxa declined in advance of the end-Cretaceous extinction. Shallow marine taxa continued diversifying in the terminal stages due to increasing sea-level. © The Geological Society of London 2011.